Simple Bond-Graph Model To Predict Dried Material Temperature Evolution in A Batch Type Rotary Dryer - Sugeng Waluyo; Ardiansyah Ardiansyah; Nurul Latifasari; Condro Kartiko; Poppy Arsil; Rumpoko Wicaksono; Muhammad Syaiful Aliim; Rifda Naufalin (JMES: The International Journal of Mechanical Engineering and Sciences, 2024)
In this work, we model temperature evolution inside a batch type rotary dryer by using the bond-graph method. The evolution model proposed here is mainly developed to predict dried material temperature inside the dryer during drying process. We implement the model in the 20-SIM bond-graph simulator (Controllab Products, the Netherlands) which shows realistic behaviors of the dried material temperature evolution with different combustion scenarios and rotation speeds.